ANTESEDEN KINERJA KARYAWAN PADA PT. SANCA SUMBER SEMEN - Alam Sanca; Mahmud Mahmud; Diana Aqmal; Nanda Adhi Purusa (Politeknik Negeri Ambon, 2026)
Introduction: Employment contracts in the mining sector require employees to work away from home, determining the duration of their presence at the worksite, which typically spans several weeks or even months. This arrangement results in prolonged absence from their families and communities. Job performance is a critical aspect of organizational behavior, with higher levels of performance associated with fewer errors. In the mining industry, companies can sustain optimal working conditions despite the potential for human error arising from low individual performance, provided that overall performance levels remain high. The purpose of this study is to examine the effects of work–family conflict and family–work conflict on employee performance, with emotional exhaustion as a mediating variable, among employees of PT Sanca Sumber Semen, Indonesia. Method: This study adopts a quantitative research design, in which data are collected using a structured questionnaire employing a five-point Likert scale. A purposive sampling technique is applied, yielding a final sample of 160 employees of PT Sanca Sumber Semen. To test the proposed hypotheses, data are analyzed using partial least squares structural equation modeling (PLS-SEM).Results: The empirical results indicate that work–family conflict and family–work conflict have a positive and significant effect on emotional exhaustion. Furthermore, work–family conflict, family–work conflict, and emotional exhaustion negatively affect employee performance at PT Sanca Sumber Semen. These findings support the Conservation of Resources (COR) theory, which posits that when employees’ internal resources (such as emotional energy, time, and attention) are depleted by role conflict and emotional exhaustion, their capacity to maintain high performance declines significantly. Keyword: Employee Performance, Emotional Fatigue, Family-Work Performance, Work-Family Performance